Determinansi Kebijakan Hutang Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2018-2022 - Amelia Setyawati; Moehammad Nasri Abdoel Wahid; Soehartatiek Soehartatiek; Dwi Kurniawan Effendi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Manufacturing companies on the Indonesia Stock Exchange (BEI) face various challenges in managing their financial policies, especially in making decisions related to dividend policy, profitability, liquidity and growth. This phenomenon shows the complexity in maintaining an optimal balance between dividend policy, profitability, liquidity and company growth. This research aims to identify and analyze the influence of dividend policy, profitability, liquidity and company growth on debt policy. The aim of this research is to analyze and measure the influence of dividend policy, profitability, liquidity and company growth on the debt policy of manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2022 period. This research uses a quantitative approach by collecting financial data from manufacturing companies listed on the IDX during that period. The data analysis technique involves statistical regression to measure the relationship between dividend policy, profitability, liquidity and company growth and debt policy. The results of data analysis show that there is a significant influence of dividend policy, profitability, liquidity and company growth on debt policy. The implication of these findings is that companies need to holistically consider these factors in financial decision making to ensure the optimality of their financial structure. This research contributes to the understanding of the factors that influence the debt policies of manufacturing companies in Indonesia. The practical implication is that company management can use these findings as a guide to optimizing their financial structure, which in turn can improve company performance and shareholder value. These findings can also provide new insights for regulators and academics in designing policies that support company growth and sustainability.